Conferencias del curso 1955-56: Wanda Hanke, Moreno Alvalat, Edwin Palm, José A. Balseiro, Tom Zuidema, Santiago Montero Díaz, Rodolfo Varón Castro, Ruiz Trapero, Ugarte, Lira Girón. - Conferencias, CONFERENCIAS (Revista Española de Antropología Americana, 1956)
Sin resumen